The Effect of Animated Health Education Videos on Menarche Preparedness Among Adolescent Girls at SDN Talaga Kulon I: Pengaruh Video Animasi Pendidikan Kesehatan terhadap Kesiapan Menarche pada Remaja Putri di SDN Talaga Kulon I - Purnamasari, Tintin (Journal of Society and Development, 2025)
Menarche marks the onset of menstruation in adolescent girls, yet many lack sufficient knowledge to face it confidently, potentially impacting their physical and emotional health. This study aims to evaluate the effectiveness of animated video media in improving knowledge about menarche among female students at SDN Talaga Kulon I. A quantitative descriptive method was used involving five sixth-grade students who had not yet experienced menarche. Data were collected through pre-test and post-test assessments following a health education intervention using animated videos. The results revealed a significant improvement in knowledge levels: before the intervention, 100% of participants had low knowledge, while after the intervention, 60% achieved good knowledge and 40% moderate knowledge. These findings suggest that animated video media can serve as an effective educational tool in increasing menarche awareness among pre-adolescent girls. This study contributes to the development of engaging, age-appropriate reproductive health education strategies in elementary school settings.